2019
DOI: 10.17811/rifie.48.3.2019.321-330
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del desempeño docente en la educación para el emprendimiento en un contexto español

Abstract: La precariedad laboral actual y la ausencia de iniciativa emprendedora en los jóvenes hacen necesario el fomento de una educación para el emprendimiento  en el espacio escolar para despertar en los discentes la creatividad, la innovación, la autonomía y la búsqueda de oportunidades. El objetivo de este estudio es conocer el estado actual de la educación para el emprendimiento en el profesorado de centros educativos de Granada (España). Para ello, se ha empleado  un cuestionario ad hoc para la recogida de datos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
2
0
3
Order By: Relevance
“…Some previous research, following this pattern, have shown how being in possession of this knowledge has led to a significant change in the teaching staff in the methodology employed and to an improvement in the perceived quality of the centre (Schildkamp & Ehren, 2012). This change is necessary inasmuch as recent studies, like Belmonte et al (2019) show how teaching staff still use a more traditional methodology with a theoretical approach for the treatment of entrepreneurial competence in the classroom. fact that can cause demotivation in their students.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous research, following this pattern, have shown how being in possession of this knowledge has led to a significant change in the teaching staff in the methodology employed and to an improvement in the perceived quality of the centre (Schildkamp & Ehren, 2012). This change is necessary inasmuch as recent studies, like Belmonte et al (2019) show how teaching staff still use a more traditional methodology with a theoretical approach for the treatment of entrepreneurial competence in the classroom. fact that can cause demotivation in their students.…”
Section: Discussionmentioning
confidence: 99%
“…In short, evidence from Students4Change suggests that although HEIs in Latin America have developed different educational responses in relation to SI, there is still a widespread feeling today that there is a need to formalise a programme specifically designed to promote SI and SE and to train universities in that endeavour. Moreover, in order to incorporate SI within universities, backing up the idea of López-Belmonte et al [41], specific training programs on SI and SE are needed not just for students but also for teachers. Teachers and students should acquire competences to, firstly, interpret a social problem; secondly, assimilate or transform the interpretation, integrating the knowledge into prototypes, products, services, or methods that provide answers to the problem that we want to solve; and thirdly, experiment with and transfer solutions and evaluate their impact [42].…”
Section: Discussionmentioning
confidence: 99%
“…Por tanto, desde la formación inicial de maestras y maestros se considera el desarrollo de competencias que doten al profesorado de la capacidad para desempeñar procesos de enseñanza de calidad y trascendencia para responder con mayor flexibilidad a las demandas del mercado laboral en continuo cambio (Sánchez et al, 2011). Entre ellas, se plantea como deseable que la educación emprendedora ocupe un lugar en las aulas universitarias, y que, a través de los proyectos y programas universitarios se busque desarrollar prácticas emprendedoras como medio para mejorar las condiciones de la sociedad en su conjunto (López-Belmonte et al, 2019).…”
Section: Introductionunclassified